Undocumented immigrants' and immigrant women's access to healthcare services in the Basque Country (Spain) - Iratxe Pérez-Urdiales (Taylor & Francis Group, 2021)
Background Immigrant populations experience diverse barriers to access healthcare services in the host countries. Among them, undocumented immigrants have more restricted legal access conditions and higher risk of having poorer health. Likewise, women are more likely to seek healthcare and face gender-based factors that hinder their access. Objective This thesis analysed the access of undocumented immigrants and immigrant women to public healthcare services in the Basque Country (Spain). Methods The thesis contained three sub-studies, carried out with qualitative and quantitative methods. For the quantitative approach, the trend in the number of consultations in a free clinic for undocumented immigrants was analysed before and after the launch of a new law, using a negative binomial regression analysis (n = 9,272). For the qualitative approach, qualitative content analysis was applied to 25 in-depth interviews with 14 immigrant women and 11 free clinic healthcare professionals. Results No clear relationship was found between the application of more restrictive legal conditions for immigrants to access public healthcare services and the trend of attendance of undocumented immigrants to a free clinic. Access of undocumented immigrants and immigrant women to healthcare services was subject to barriers dependent on their characteristics, health system functioning, legal requirements and a stereotyped and poor social consideration of immigrants, shared by professionals at the health centres. Meanwhile, provision of legal information and support by individual professionals, social organizations and personal networks represented main facilitators for accessing. Conclusions For the access of undocumented immigrants and immigrant women, structural and individual barriers based on their social vulnerability were found. Among others, gender-based violence reduced women's possibility to access healthcare services and being undocumented led to restricted access entitlement and to fear rejection at health centres. Therefore, besides ensuring immigrants' legal entitlement, there is need of promoting rights-based attention to get more inclusive health systems.